(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2013)
Clinical features of Systemic Lupus Erythematosus (SLE) worsens when it involves kidneys. Even then in our socioeconomic context the patients who seek admission are usually at later stages. Moreover histological classes may not be previewed by clinical and laboratory features. The aim of the study is to show variation of clinical features and laboratory findings in relation to pathological classes of Lupus nephritis. It was a cross sectional descriptive study enrolling 30 female patients admitted in medicine and nephrology department of Chittagong Medical College. Majority of the patients are of age range 21-40 years (73%); belonging to middle class family (90%) and educated upto level of secondary school certificate (43%). Oedema (93%), normotension (73%) and anaemia (93%) are common clinical features. Though all patients had macroscopic proteinuria only 20 % patients had massive proteinuria (>3gm%). Serologically Nineteen patients are ANA positive (63%) and all patients had Anti-dsDNA positivity. Class III and Class IV comprises 70% of patients. Estimated Glomerular filtration rate (eGFR) is more in class V ( mean 77.77) and class III (mean 76.86) than class II ( mean 52.67) and class IV ( mean 59.95) signifying eGFR cannot estimate severity. In conclusion without renal biopsy Lupus nephritis class cannot be ascertained and so class specific management cannot be given. JCMCTA 2012 ; 23 (2): 34-37